Expert Consensus on a Proposed Study Framework to Explore Factors Influencing Plasmodium knowlesi Malaria Preventive Behavior: A Modified Delphi Method Protocol - Nurul Athirah Naserrudin; Rozita Hod; Mohammad Saffree Jeffree; Kamruddin Ahmed; Mohd Rohaizat Hassan (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The increasing incidence of P. knowlesi malaria infection among humans is a public health threat. This zoonotic disease is challenging to eliminate owing to the presence of animal reservoirs. Understanding the factors such as the community’s belief, social context, drivers, and barriers can provide insights into malaria preventive behavior. It is crucial to improve the current preventive measures. This study aims to achieve consensus among malaria experts based on evidence from literature reviews and experts’ opinions on possible factors influencing malaria preventive behavior among communities exposed to P. knowlesi malaria infection. A modified Delphi study protocol was developed to gather experts’ consensus on the study framework to explore the factors influencing preventive behavior among communities exposed to P. knowlesi malaria infection. The framework is adapted from the ideation model, and it is integrated with other relevant theories and extensive literature reviews. We will use the modified Delphi protocol to reach a consensus. The experts will respond to each questionnaire item and a related open-ended questionnaire. Consensus is predetermined at more than 70% agreement on the items. We will use descriptive statistics and thematic analysis to analyze the data. All experts will remain anonymous to maintain the characteristics of a traditional Delphi study.